Distribution of Soil Physical Characteristics Across Different Slope Gradients in Highland Areas (Tawangmangu, Indonesia) for Potato Crop Development - Sumani Sumani; Dwi Priyo Ariyanto; Ganjar Herdiansyah; Maria Theresia Sri Budiastuti; Anita Yulianti; Viviana Irmawati; Tiara Hardian; Nanda Mei Istiqomah (Acta Solum, 2025)
Tawangmangu District, Indonesia, is located in a highland area with a cool climate and is predominantly composed of Andisol soil types, offering great potential for the development of potato crops (Solanum tuberosum L.). This study aims to examine soil physical properties suitable for potato cultivation, analyze the distribution of these properties across different slope gradients, and identify appropriate soil management strategies for the Tawangmangu area. The research employed a descriptive-exploratory approach, utilizing land map units (LMUs) that were determined through the overlay of soil type maps, rainfall data, slope gradients, and land use. The overlay resulted in 5 LMUs and 25 sampling points. Observed soil physical parameters included texture, porosity, permeability, consistency, effective soil depth, coarse material, and drainage. The land suitability assessment showed that LMUs 1, 2, and 3 were classified as S3-oa, limited by drainage, while LMUs 4 and 5 were classified as S3-oa,rc, limited by both drainage and effective soil depth. Slope gradient significantly affected moisture content (p = 0.022), bulk density (p = 0.037), particle density (p = 0.048), porosity (p = 0.032), effective soil depth (p = 0.001), and coarse material content (p = 0.032). Recommended land management efforts include the addition of organic matter, manual tillage for shallow soils, and the application of eco-drainage techniques to improve soil physical suitability for potato cultivation in Tawangmangu.